Performance optimization of doubly-fed induction generator (DFIG) equipped variable-speed wind energy turbines by using three-level converter with adaptive fuzzy PI control system. (2021) - Kasbi, Abdellatif; Rahali, Abderrafii
Abstract: The present paper aims at optimizing the performance of a Doubly Fed Induction Generator (DFIG) equipped variable-speed wind energy turbine in utility grid-connected mode. Since maximum power extraction and output power quality improvement are considered the main challenges for enormous scale variable-speed wind turbines to meet the worldwide demand for clean energy, this work has two contributions; the first concerns the use of the three-level converters to upgrade the output power quality of the wind energy turbine through reducing the total harmonic distortion (THD) of the currents delivered to the power grid, whereas the second contribution intends to design an adaptive proportional-integral (PI) control system for the rotor side converter (RSC) control. The proposed adaptive PI control system is designed by combining the intelligent and adaptive nature of fuzzy logic control (FLC) and the simpleness of the PI controller framework to effectively optimize the DFIG wind energy turbine performance. In the proposed control system, the PI controller's gains are adjusted in real-time by a supervisory system based on FLC according to the wind turbine running conditions. The adopted control scheme to controlling the RSC comprises two cascaded regulation loops for reaching the maximum power point tracking (MPPT), that intends to extract obtainable maximum power of the wind energy turbine. The internal regulation loop is applied to control the rotor current while the external regulation loop is employed to regulate the generator speed. To prove the efficiency of the three-level converter and performance of the proposed control system, simulation studies were performed utilizing MATLAB/Simulink software. The obtained results through simulation clearly show that research paper purposes are achieved and the performance optimization of the wind turbine is well done.